(untitled) (Journal of Oriental Studies, 2019)
In this study, in a certain degree we came to a contradicting or rather complementing the conclusions of earlier studies, or to be exact, we found “traces” of Turkic tribes in the ancient Indian literature and their participation in formation of the ancient Indian civilization and culture. Continuity of relations between the Turkic and Indian literature with a long history is important in history of development of our spiritual culture and artistic development of literature. Therefore, the study of literary relations between nations and history of their formation will serve as a source for expanding the scientific and theoretical aspect of the research. The article attempts to consider conclusions, which suggest that the ancient Indian culture and literature formed in result of the synthesis of various tribes and national heritage. Among the tribes as an example, we dwell on the Dravidians and Aryans, who inhabited the Indus Valley in the III century. Therefore, in our study to determine the Dravidian and Aryan tribes, we will focus on historical review of each tribe that played a role in development of literary genres. Key words: India, heritage, literature, culture, civilization, Dravid and Aryan tribes.